(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Vitamin D is a fat soluble vitamin, having important role in calcium and phosphorous metabolism. Many researches support the role of vitamin D against cancer, cardiovascular diseases, fractures and falls, cognitive disorders, Parkinsonism, auto-immune diseases, respiratory ailments and depression. Thus Vitamin D Deficiency (VDD) is an alarming public problem. Purpose of this study was to measure the frequency of hypovitaminosis D among different age and sex group of Chattogram, Bangladesh. Materials and methods: A cross sectional hospital based observational study was conducted over a period of six months from February 2018 to July 2018 at a leading diagnostic complex and hospital of Chattogram. A total of 243 patients were included in the study. Number of male and female respondents were 86 and 157 respectively. Age range was 15-85 years. Blood samples were collected aseptically after an oral informed consent. Serum vitamin D levels were estimated using standard laboratory technique (Chemiluminescent microparticle immunoassay method). Results: Among 243 respondents, male female ratio was 1:1.83, mean age was 47± 16.3 years, prevalence of hypovitaminosis was 82%, among male hypovitaminosis was found in 78% cases, whereas among female it was a bit higher with 84%. Sex difference was strongly significant with p value of < 0.01. Conclusion: The present study has limitation with estimation of only vitamin D, in absence of valuable indicators of bone health like serum calcium, bone mineral density and parathyroid hormone. Factors like, less outdoor activities, obesity or covering whole body (Abaiya or burkah) in case of Muslim women, which could be responsible for more hypovitaminosis in case of female was not noticed. But it was very much clear that 45-60 years age group was the most vulnerable with highest level of hypovitaminosis-D in both sexes. Chatt Maa Shi Hosp Med Coll J; Vol.18 (2); July 2019; Page 37-40